User Experience Optimization Researcb on Personalized Pusb Approacb of IPTV Service Based on Label of Contents - Yingbo Zhu; Jianwei Diao; Bo Kang; Shengqiang Liu (Dianxin kexue)
iMusci Karaok is a service on IPTV developed and operated by China Telecom. It is needed to introduce active personalized push approach of content in order to improve user experience, due to higher cost of remote controller than PC and mobile phone. However, Karaok is a household service, and is ununiform to identify users on server side and terminal side, which will bring inaccurate result when normal recommendation algorithm is adopted. Meanwhile, traditional recommendation algorithm has defects of Matthew effect and cold reboot, which will decrease user experience. To tackle such problems of user experience, the recommendation algorithm was selected and optimized by combination of content label so as to increase recommendation objectively. This research is aiming at enhancing user experience effect rather than algorithm complexity.